A Longitudinal Analysis of the Association Between Living Arrangements and Health Among Older Adults in China. (January 2018) - Zhou, Zi; Mao, Fanzhen; Ma, Jiaping; Hao, Shichao; Qian, Zhengmin (Min); Elder, Keith; Turner, Jason S.; Fang, Ya
This article used the nationally representative Chinese Longitudinal Healthy Longevity Survey to explore the associations between living arrangements and health among older adults. Living arrangements were stratified into six categories. Health was measured by self-rated health, activities of daily living (ADL) disability, and cognitive impairment. Random-effects ordered probit regressions were applied. The results indicated that coresidence had a positive effect on self-rated health compared with living alone. After introducing psychological well-being, the health differences observed in living with a spouse and living with both spouse and children were not significant. Participants with each of the living arrangement were more likely to have a higher rate of cognitive impairment and ADL disability than those living alone. Living arrangements were associated with older adults' health. Psychological well-being was a key factor in this association, which may result from living with a spouse, and could contribute to the self-rated health of older adults.